Management of Hypertension in Patients with Chronic Kidney Disease in Asia - Huang, Qi-Fang; Hoshide, Satoshi; Cheng, Hao-Min; Park, Sungha; Park, Chang-Gyu; Chen, Chen-Huan; Kario, Kazuomi; Wang, Ji-Guang; on behalf of the Characteristics On the Management of Hypertension in Asia-Morning Hypertension Discussion Group(COME Asia MHDG) (Current Hypertension Reviews, 2016)
Hypertension is both a cause and consequence of chronic kidney disease (CKD). According to the Chinese national survey in 2007-2010, the prevalence of CKD was much higher in hypertensive patients (18.9%, n=16,691) than in the overall population sample (10.8%, n=47,204). CKD in hypertension confers risks to the kidneys as well as other organs. Probably because of high dietary salt intake, Asian hypertensive patients with CKD show high prevalence of non-dipping and reversed dipping blood pressure pattern, and may have even higher risks of cardiovascular disease. Therefore, out-of-office blood pressure evaluation and comprehensive cardiovascular evaluations are required. Most of current hypertension guidelines recommend intensive antihypertensive treatment in hypertensive patients with CKD. This is probably of particular relevance for cardiovascular prevention in Asia, because stroke, as a major complication of hypertension in Asia, is more closely related to blood pressure than coronary events. Intensive blood pressure control to 130/80 mmHg is often required to prevent CKD progression and cardiovascular complications. The inhibitors of the renin–angiotensin system (RAS) are recommended as the first line antihypertensive medications in patients with a glomerular filtration rate higher than 30 ml/min/1.73 m², which may more efficaciously prevent end-stage renal disease and cardiovascular events. Nonetheless, combination therapy of RAS inhibitors with other classes of antihypertensive drugs, such as calcium-channel blockers, diuretics, etc, is required to control blood pressure to the target.
Keywords: Hypertension